Association of Maternal Serum Zinc with Risk of Preeclampsia: A Comprehensive Systematic Review - Brigitta; Selvia (The International Journal of Medical Science and Health Research, 2024)
Background: Zinc is an essential trace mineral element vital for many physiological functions and plays an important role in growth, reproduction, and the immune system. Adequate zinc stores in the body are extremely important during periods of pregnancy. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: serum zinc level in PE patients was significantly lower than that in healthy pregnancy women. A moderate amount of zinc supplementation may reduce the incidence of PE, which needs to be confirmed.